Statistical Analysis of the Tensile Strength of Coal Fly Ash Concrete with Fibers Using Central Composite Design - Marinela Barbuta; Emanuela Marin; Sorin Mihai Cimpeanu; Gigel Paraschiv; Daniel Lepadatu; Roxana Dana Bucur (Advances in Materials Science and Engineering)
The influence of coal fly ash and glass fiber waste on the tensile strength of cement concrete was studied using central composite design. Coal fly ash was used to replace 10% of the cement in the concrete mix. Glass fiber was added to improve the tensile properties of the concrete in different dosages and lengths. In total, 14 mixes were investigated, one only with 10% coal fly ash replacement of cement and the other thirteen were determined by the experimental design. Using analysis of variance, the order of importance of the variables was established for each property (flexural strength and split tensile strength). From the nonlinear response surfaces, it was found that higher values of flexural strength were obtained for fibers longer than 12 mm and at a dosage of 1-2%. For split tensile strength, higher values were obtained for fibers with a length of 19–28 mm and at a dosage of 1–1.5%.